Two Pediatric Patients with Herbal Medicine-Induced Nephrotic Syndrome - Sohyoung Yang; Arum Oh; Tae-Sun Ha (Korean Society of Pediatric Nephrology, 2015)
Nephrotic syndrome (NS) is a common chronic disease in children; in 90 percent of cases, the condition is primary (idiopathic). Toxic nephropathy can be induced by herbal medicines, and is mainly manifested as tubulointerstitial nephritis and rarely, as glomerulopathy. Here in, we describe two cases of steroid-sensitive NS, which developed after the patients received herbal medicines. A 5-year-old boy and an 8-year-old girl were separately admitted within a short time period with acute onset of generalized edema, proteinuria, hypoalbuminemia, and hypercholesterolemia. Each patient had previously taken herbal medicine, which had been prescribed by different oriental medical clinics for different conditions. The patients were diagnosed with herbal medicine-induced NS and were treated empirically by a standard steroid therapy, with subsequent resolution of their NS. One patient relapsed, but her NS again responded to steroid therapy. We described two unusual cases of prototypical pediatric, steroid-sensitive NS, which was presumed to be minimal-change disease that developed after the administration of herbal medicines. We also reviewed the literature.